MANAGING RISK IN SMALL STEPS: ACHIEVING LANDSLIDE RISK REDUCTION BY STRATEGIC INCREMENTALISM IN THE EASTERN CARIBBEAN. (10th July 2011) - Anderson, Malcolm G.; Holcombe, Elizabeth
Abstract Understanding landslide processes in developing counties, coupled with community engagement can deliver landslide hazard reduction 'on the ground', leading to behavioural change within communities and governments. On this basis, we undertook a 'strategic incrementalism' approach to landslide risk reduction. The change achieved in stakeholder engagement was simultaneously a major challenge and the determinant of the project success. However, the resulting stakeholder commitment demonstrates the clear benefit of designing risk reduction measures that deliver research, on‐the‐ground reduction of risk and behavioural change and provides specific evidence that strategic incrementalism is a viable process. Copyright © 2011 John Wiley & Sons, Ltd.